Comparison of Thalamus and Basal Ganglia Signs Between Multiple Sclerosis and Primary Angiitis of the Central Nervous System: An Exploratory Study - Chen, Ying; Li, Rui; Wu, Aimin; Qiu, Wei; Hu, Xueqiang; Hu, Zhaoqi; Yang, Qian; Zhou, Zhiming (Frontiers in Neurology, 2021)
Multiple sclerosis(MS) is difficult to be distinguished from primary angiitis of central nervous system (PACNS)affected with small vessels, from symptoms. Magnetic resonance imaging (MRI)helps understand the characteristics of deep grey matter lesions in MS and PACNS. We aimed to compare the MRI characteristics of thalamus and basal ganglia lesionsbetween relapsing-remittingMS and PACNS. In our study,49 relapsing- remittingMS patients and16 PACNSs with MRI-confirmed thalamus or basal ganglia lesions were enrolled. Thalamus was more prone to be affected in MS(83.7%) than PACNS(43.8%)(P=0.002). Among the DGMLs in basal ganglia, putamen had significantly higher (P=0.037) involvement in PACNS than in MS. More importantly,larger lesion sizes in thalamus helps to distinguish PACNS(12.4mm±4.3mm) from MS(7.9mm± 3.7mm)(P=0.006). But lesions in basal ganglia were unable to differentiate the two disorders. Presently, our study shows that MRI performances of deep grey matter differ in distribution and sizes in MS and PACNS.